Edukasi dan Pelatihan Manajemen Bank Sampah kepada Warga Kelurahan Oesapa Barat dan Pengurus Bank Sampah Muara Abu - Arifin Sanusi; Pius D. Ola; Yeremias M. Pell (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2026)
One of the impacts of population growth in a residential area is the problem of waste. If this problem is not immediately addressed, it will have a negative impact on residents around the settlement and the environment. This encourages collaboration from various parties, including universities and business actors of the Muara Abu Waste Bank to address this waste problem. This community service can be implemented by a team of lecturers from Nusa Cendana University with funding from the Ministry of Education, Science and Technology through BIMA. The objectives of this activity are first to provide education to residents of Oesapa Barat Village, especially around the Muara Abu coast, through waste bank management. The number of participants who attended this training was 50 residents, including waste bank customers. The second objective is to provide management training for the administrators of the Muara Abu Waste Bank (BSMA). The implementation of the activity consists of three stages: the preparation stage, the implementation stage, and the evaluation stage. The training material is the basics of waste bank management, including selection, sorting, packaging, and shipping. The following material introduces the management activities carried out during work, starting with customer deposits, sorting, weighing, storage, and bookkeeping of the waste bank account. For the waste bank administrators, the training focused on administrative systems and operational procedures. Educational activities also introduced creativity in recycled plastic waste products. The training, particularly for participants, resulted in increased knowledge of waste bank management. Before the training, only 38% of participants understood the material, whereas after the training this figure increased to 92%. Another impact was the rise in the number of BSMA customers, which grew from 39 to 68 by September 2025. This demonstrates the significant impact of this activity in raising public awareness of the benefits of waste banks.